1992
DOI: 10.1139/t92-030
|View full text |Cite
|
Sign up to set email alerts
|

Cracking in drying soils

Abstract: Cracking in soils that are undergoing drying is controlled by soil suctions and by soil properties such as compression modulus, Poisson's ratio, shear strength, tensile strength, and specific surface energy. The paper reviews the occurrence and morphology of cracks in dry-climate regions of Australia and Canada. After reviewing the behaviour of unsaturated soils and the mechanics of cracking, solutions are developed based on ( i ) elasticity theory, ( i i ) the transition between tensile and shear failure, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
236
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 454 publications
(275 citation statements)
references
References 21 publications
8
236
0
1
Order By: Relevance
“…It is found that soil fabric, particle cementation, water content and void ratio are altered significantly (Cuisinier and Masrouri 2005;Rao and Revanasiddappa 2006;Tripathy et al 2009;Tovar and Colmenares 2011;Sun and Huang 2015). These effects lead to the formation of cracks as well as the development of fissures in soils, which significantly increase soil compressibility and hydraulic conductivity and consequently decrease the overall structural strength and stability (Morris et al 1992;Albrecht and Benson 2001;Pires et al 2008;Li et al 2009;. Several researchers also reported that the impact of the first drying-wetting cycle on soil structure is D r a f t 2 greatest and decreases with subsequent cycles (Basma et al 1996;Tripathy et al 2002;Leij et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It is found that soil fabric, particle cementation, water content and void ratio are altered significantly (Cuisinier and Masrouri 2005;Rao and Revanasiddappa 2006;Tripathy et al 2009;Tovar and Colmenares 2011;Sun and Huang 2015). These effects lead to the formation of cracks as well as the development of fissures in soils, which significantly increase soil compressibility and hydraulic conductivity and consequently decrease the overall structural strength and stability (Morris et al 1992;Albrecht and Benson 2001;Pires et al 2008;Li et al 2009;. Several researchers also reported that the impact of the first drying-wetting cycle on soil structure is D r a f t 2 greatest and decreases with subsequent cycles (Basma et al 1996;Tripathy et al 2002;Leij et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This common surface phenomenon is a special case of invasion by an immiscible fluid, where air invades water-saturated sediment. Desiccation cracks typically nucleate at the surface (in homogeneous sediments) and propagate both laterally and vertically, forming vertical planes (Morris et al, 1992;Konrad & Ayad, 1997;Rodriguez et al, 2007;Thusyanthan et al, 2007;Shin & Santamarina, 2011). (d) Ice and methane hydrate lenses ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…We assume the existence of a tension cut-off expressed in terms of a minimum mean effective stress. This is a variation, expressed in terms of effective stress, of the work of Morris et al [Morris et al (1992)]. The surface that represents this failure mechanism is expressed at equation 11 and visible in Fig.…”
Section: Mechanical Modelmentioning
confidence: 99%